Body Image in Teenage Women who Are Fans of K-POP Girl Bands: A Study on Students of IAIN Palangka Raya - Surawan, Surawan; Risa, Maya (Kartika: Jurnal Studi Keislaman, 2024)
Korean culture has developed so rapidly that it has become widespread and accepted by the world public, resulting in a phenomenon of Korean culture fever at the global level, which can be referred to as the Korean Wave. This study aims to explore the understanding and experiences of female students at IAIN Palangka Raya who are fans of K-Pop girl groups in relation to body image. This qualitative research employs in-depth interviews, observations, and literature reviews with thematic analysis. The findings reveal diverse perceptions of body image and beauty standards, with the majority holding positive views. Factors influencing body image include media exposure, social comparison, social environmental pressures, as well as personality and self-esteem. Strategies used to manage pressures and expectations related to physical appearance include self-acceptance, personal development in other areas, seeking social support, and forming positive fan communities. This research highlights the significant role of social media and interactions within fan communities in shaping body image perceptions. The results provide new insights into the impact of popular culture on body image among adolescent girls and the strategies employed to cope with appearance-related pressures.